A atuação de Dom José Ivo Lorscheiter durante a ditadura civil-militar brasileira (1964-1985) - Torres, Thiago Alves (2017)
This work presents a study about the performance of the Catholic bishop Dom José Ivo Lorscheiter during the Brazilian civil-military dictatorship (1964-1985). Through this, it is searched to emphasize the protagonism assumed by the religious in the defense of human rights. The research is based on a bibliographical data of the presence of the Catholic Church in Brazil, starting with the Proclamation of the Republic and with the historiographical contextualization of two ecclesiastical events that influenced the pastoral practice and the trajectory of Dom José Ivo Lorscheiter, the Vatican Ecumenical Council II, held in Vatican (1962-1965), and the Second General Conference of the Latin American Episcopate, held in Medellín, in Colombia (1968), events that provoked theoretical and structural changes for the Church in Latin America, and demand from the Catholic Church a position focused on the defense of human rights. Our investigation is centered on the role of the prelate after assuming prominent positions at the Brazilian National Bishops' Conference (CNBB), first as general secretary, and then as president of the organization in both situations for two consecutive terms when we inquire about the position of the prelate in the period of the Brazilian civil-military dictatorship and the participation of the Catholic Church in the civil-military pre-coup and, later, in the civil-military dictatorship. With the help of Michel Foucault, we can say that the political discourse adopted by the religious is a consequence of his first pastoral and then social practice. Together with the CNBB, he had to make himself present and express himself as a result of situations that affected laymen and clerics, regarding the violation of human rights. To do so, we search subsidies in newspaper sources, magazines and documents deposited in archives. In addition, by appropriating the contributions of Pierre Bourdieu, we seek to understand the ideological function of religions. In our investigation, we focused on analysis in Catholicism, which sought, especially in the period before the Second Vatican Council, to absolutize dogmas and impose principles that became unquestionable and opposed to temporal changes, and which were defended by members of the Church's leadership Prior to the Second Vatican Council. In both the post-Vatican I and post-Vatican II period and the Medellin Conference, the Catholic Church sought to form its members, first, in the unrestricted view of self-preservation, and years later, while remaining in the vicinity of the people who were suffering from the most diverse forms of rape and marginalization.